2011
DOI: 10.2298/sarh1104149m
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and chronic bronchitis symptoms among adult population of Belgrade

Abstract: In Serbia there is a high prevalence of respiratory symptoms, asthma and chronic bronchitis smoking addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
3
16
0
1
Order By: Relevance
“…In the territory of Belgrade, the prevalence of asthmatic symptoms in the adult population amounts to 12.5% [15]. In our study, the diagnosis of asthma was confirmed in 455 (22%) subjects.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In the territory of Belgrade, the prevalence of asthmatic symptoms in the adult population amounts to 12.5% [15]. In our study, the diagnosis of asthma was confirmed in 455 (22%) subjects.…”
Section: Discussionsupporting
confidence: 66%
“…The reported data emphasize the need for continuous education in the field of asthma and COPD, so that the diagnosis may be established in compliance with current diagnostic criteria, based on spirometry tests because In our study, one third of the patients with asthma and one half of COPD patients were active smokers. Milenkovic et al reported similar findings [15]. Tobacco smoke is the most frequent, preventable risk factor for pulmonary diseases [23].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The prevalence of this disease is also high in Serbia [36]. The prevalence of this disease is also high in Serbia [36].…”
Section: Preventive Measures and Early Detection Of Atherosclerosis Amentioning
confidence: 94%
“…According to the Global Initiative for Chronic Obstructive Lung Disease guidelines, more than half of patients with this disease remain undiagnosed [37]. That is why family doctors play a crucial role in the health care system, because they can integrate physical, psychological, social, cultural and existential characteristics of patients in order to diagnose the disease as early as possible [36]. That is why family doctors play a crucial role in the health care system, because they can integrate physical, psychological, social, cultural and existential characteristics of patients in order to diagnose the disease as early as possible [36].…”
Section: Preventive Measures and Early Detection Of Atherosclerosis Amentioning
confidence: 99%